2011
DOI: 10.1007/s13197-011-0266-7
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modelling of thin layer hot air drying of carrot pomace

Abstract: Thin layer carrot pomace drying characteristics were evaluated in a laboratory scale hot air forced convective dryer. The drying experiments were carried out at 60, 65, 70 & 75 °C and at an air velocity of 0.7 m/s. Mathematical models were tested to fit drying data of carrot pomace. The whole drying process of carrot pomace took place in a falling rate period except a very short accelerating period at the beginning. The average values of effective diffusivity ranged from 2.74 × 10(-9) to 4.64 × 10(-9) m(2)/s f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 29 publications
14
52
0
Order By: Relevance
“…As expected, the values of D eff increased with the increase of output power. This result is similar to the results for carrot pomace (Kumar et al 2012), apple pomace , and tomato by-products ( …”
Section: Effective Moisture Diffusivitysupporting
confidence: 90%
See 1 more Smart Citation
“…As expected, the values of D eff increased with the increase of output power. This result is similar to the results for carrot pomace (Kumar et al 2012), apple pomace , and tomato by-products ( …”
Section: Effective Moisture Diffusivitysupporting
confidence: 90%
“…As expected, the values of D eff increased with the increase of output power. This result is similar to the results for carrot pomace (Kumar et al 2012), apple pomace , and tomato by-products (Ruiz Celma et al 2009b). The effect of infrared power on effective diffusivity is defined by the following equation: …”
Section: Fitting Of the Drying Curvessupporting
confidence: 84%
“…Using thin layer drying the sample is dried in a single layer, which results in faster removal of moisture (6). A number of studies have been conducted on drying kinetics of diff erent fruits and vegetables such as apricot (7), seedless grape (8), sweet potato (9) and yam slices (10), so that they can be preserved by reducing the moisture content with minimal loss in valuable phytonutrients along with chemical and microbiological stability.…”
Section: ) Shredsmentioning
confidence: 99%
“…For longer drying period, Eq. 10 can be further simplifi ed to only the fi rst term of series (6,19) and can be writt en as follows: …”
Section: Eff Ective Moisture Diff Usivity and Activation Energymentioning
confidence: 99%
“…These models can be categorized as theoretical, semi-theoretical, and empirical [11]. Several mathematical modelling and experimental studies have been revealed concerning the drying characteristics of fruit and vegetable pomaces, such as grape pomace [12], tomato pomace [10,13], carrot pomace [14], and olive pomace [15,16]. So far, there a little information available about Abstract Drying of apple pomace representing byproducts from apple juice processing was studied.…”
mentioning
confidence: 99%